Obesity and immune-checkpoint inhibitors in advanced melanoma: A meta-analysis of survival outcomes from clinical studies. (June 2023) - Roccuzzo, Gabriele; Moirano, Giovenale; Fava, Paolo; Maule, Milena; Ribero, Simone; Quaglino, Pietro
Abstract: Obesity is a chronic inflammatory condition that has been associated with different types of cancer. However, its role in melanoma incidence, progression, and response to immune-checkpoint-inhibitors (ICI) is still controversial. On the one hand, increased levels of lipids and adipokines can promote tumor proliferation and several genes associated with fatty acid metabolism have been found to be upregulated in melanomas. On the other hand, immunotherapy seems to be more effective in obese animal models, presumably due to an increase in CD8 + and subsequent decrease in PD-1 + T-cells in the tumor microenvironment. In humans, several studies have investigated the role of BMI (body mass index) and other adiposity-related parameters as potential prognostic markers of survival in advanced melanoma patients treated with ICI. The aim of this research has been to systematically review the scientific literature on studies evaluating the relationship between overweight/obesity and survival outcomes in patients with advanced melanoma treated with ICI and to perform a meta-analysis on those sharing common characteristics. After screening 1070 records identified through a literature search, 18 articles assessing the role of BMI-related exposure in relation to survival outcomes in ICI-treated patients with advanced melanoma were included in our review. In the meta-analysis of the association between overweight (defined as BMI>25 or BMI 25–30), overall survival (OS), and progression free survival (PFS), 7 studies were included, yielding a summary HR of 0.87 (95% CI: 0.74–1.03) and 0.96 (95% CI: 0.86–1.08), respectively. Our results show that, despite few suggestive findings, the use of BMI as a valuable predictor of melanoma patients' survival in terms of PFS and OS should not be currently recommended, due to the limited evidence available.